Dropping the devil's advocate: One novice language tester's shifting interactional practices across a series of speaking tests. Issue 1 (2nd January 2016) - Leyland, Christopher; Greer, Tim; Rettig-Miki, Ellen
Abstract : This study employs longitudinal Conversation Analysis (CA) to examine one TA's follow-up contributions in a series of EFL group discussion tests. By tracking the TA's interactional practices across 18 groups, we observe how she adapts her turn design by increasingly aligning towards that of the novice English speakers. The TA initially attempts to make use of rhetorical discourse structures, such as by playing devil's advocate and providing up-shot summaries of the test-takers' prior talk; however, a detailed sequential analysis of the talk reveals that such strategies do not generate significant follow-up turns from the students. Adopting a longitudinal CA approach demonstrates the way the TA, as a novice language teacher, develops her pedagogical tactics in situ according to the style and level of the students with whom she is interacting. As such, the study provides insight into one novice professional's natural acquisition of teaching skills, and, more generally, into the way that speakers adapt their interactional practices across multiple and subsequent episodes of a given conversation.